Parental Feeding Practices among Brazilian School-Aged Children: Associations with Parent and Child Characteristics - Mais, Laís Amaral; Warkentin, Sarah; Latorre, Maria do Rosário Dias de Oliveira; Carnell, Susan; Taddei, José Augusto Aguiar de Carrazedo (Frontiers in Nutrition, 2017)
Background Children’s eating behavior, food intake and weight status are highly influenced by parents, who shape their food environment via parental feeding practices. The aim of this study was to investigate associations between sociodemographic, anthropometric and behavioral/attitudinal characteristics of parents and their 5-to-9 year-old children, and a range of positive (“healthy eating guidance”, “monitoring”) and potentially negative (“restriction for weight control”, “restriction for health”, “emotion regulation/food as reward”, “pressure”) parental feeding practices. Methods Parents completed a questionnaire assessing parental and child characteristics. Parental feeding practices were measured using a Brazilian adaptation of the Comprehensive Feeding Practices Questionnaire. To test associations between parent and child characteristics, and parental feeding practices, we ran bivariate logistic regression models with parent and child characteristics as independent variables and high (above median) scores on individual parental feeding practices as outcome variables. We then conducted multivariate logistic regression models containing all parent and child characteristics, controlling for child age and maternal education. Results Lower parental perceived responsibility for child feeding, higher child use of screen devices, and higher child ultra-processed food intake were associated with lower scores on “healthy eating guidance” and “monitoring”. Higher parental perceived responsibility for child feeding and concern about child overweight were associated with higher scores on “restriction for weight control” and “restriction for health”. Parental perceptions of low weight and concern about child underweight, and higher perceived responsibility for child feeding, were associated with higher scores on “pressure”. Greater intake of ultra-processed foods, and lower maternal age were associated with higher scores on “emotion regulation/food as reward”. Conclusions Parental concerns and perceptions relating to child weight were predictive of potentially negative feeding practices. Higher scores on potentially negative feeding practices, and lower scores on positive parent feeding practices, were associated with poorer child diet and higher use of screen devices. Parental engagement in the feeding interaction predicted greater adoption of both potentially negative and positive feeding practices. These results support the need for policies and programs to educate parents about child feeding and help motivated parents to promote healthy lifestyles in their children.